2018
DOI: 10.21273/hortsci13079-18
|View full text |Cite
|
Sign up to set email alerts
|

Application of Foliar Synthetic Elicitors for the Management of Diaphorina citri (Hemiptera: Liviidae) Populations in Tahiti Lime (Citrus latifolia Tanaka)

Abstract: The Asian citrus psyllid (ACP), Diaphorina citri Kuwayama, is the most serious threat to the global citrus industry, and its management has depended mainly on the application of chemical insecticides. The application of plant elicitors can contribute to the insect management and also enhance plant physiology. A set of three different experiments was carried out to evaluate the efficacy of foliar applications of synthetic elicitors [salicylic acid (SA), brassinosteroids (Br), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The use of particle film barriers Particle films reduce insect damage by covering organs, such as leaves. Foliar spray of kaolin clay-and calcium carbonate-based particle films significantly reduced the population levels of psyllid adults, nymphs, and eggs on citrus trees compared to the untreated control in field trials in Colombia (Ramírez-Godoy et al 2018). In this study, foliar applications of kaolin clay showed similar effectiveness as the imidacloprid insecticide in reducing populations of psyllid eggs (Ramírez-Godoy et al 2018).…”
Section: Strategies Targeting the Acp Vectorsupporting
confidence: 52%
See 2 more Smart Citations
“…The use of particle film barriers Particle films reduce insect damage by covering organs, such as leaves. Foliar spray of kaolin clay-and calcium carbonate-based particle films significantly reduced the population levels of psyllid adults, nymphs, and eggs on citrus trees compared to the untreated control in field trials in Colombia (Ramírez-Godoy et al 2018). In this study, foliar applications of kaolin clay showed similar effectiveness as the imidacloprid insecticide in reducing populations of psyllid eggs (Ramírez-Godoy et al 2018).…”
Section: Strategies Targeting the Acp Vectorsupporting
confidence: 52%
“…Foliar spray of kaolin clay-and calcium carbonate-based particle films significantly reduced the population levels of psyllid adults, nymphs, and eggs on citrus trees compared to the untreated control in field trials in Colombia (Ramírez-Godoy et al 2018). In this study, foliar applications of kaolin clay showed similar effectiveness as the imidacloprid insecticide in reducing populations of psyllid eggs (Ramírez-Godoy et al 2018). Studies performed under laboratory and field conditions revealed that processed kaolin interferes negatively with different aspects of the ACP's ability to find the host plant, resulting in a reduced adult population on treated citrus plants (Miranda et al 2018).…”
Section: Strategies Targeting the Acp Vectormentioning
confidence: 95%
See 1 more Smart Citation
“…The use of synthetic elicitors can be considered an effective tool to mitigate the negative effects generated by abiotic and biotic stresses in plants (Llorens et al, 2017;Naik and Al-Khayri, 2016). Elicitors are chemical compounds that can be sprayed on leaves, causing a stimulus on plant defense mechanisms and secondary metabolite synthesis under abiotic and biotic stress conditions (Llorens et al, 2017;Ramírez-Godoy et al, 2018;Thakur and Sohal, 2013). SA, BR, and plant BEs have been studied and characterized as compounds that activate plant defense mechanisms against stress conditions (abiotic and biotic) (Bektas and Eulgem, 2015;Singh et al, 2017;Vardhini and Anjum, 2015;Xue et al, 2013;Zhang et al, 2015).…”
mentioning
confidence: 99%
“…Plant resistance induction under abiotic and biotic stress conditions can be regulated by physiological, biochemical and molecular mechanisms [13,58]. Similarly, these plant resistance responses can be stimulated by exogenous synthetic elicitors application [59,60]. The present study showed that the foliar application of synthetic elicitors, mainly BR (1 mL L −1 ), SA (100 mg L −1 ) or BE (2.5 mL L −1 ), helped to mitigate the negative effects caused by Foph by favoring physiological and biochemical responses in cape gooseberry plants.…”
Section: Discussionmentioning
confidence: 99%